2016
DOI: 10.1111/acer.13155
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Affective and Cognitive Theory of Mind in Recently Detoxified Alcohol‐Dependent Individuals

Abstract: Ecological ToM evaluation shows that alcohol dependence is not related to a generalized ToM deficit but rather to dissociation between a preserved cognitive subcomponent and an impaired affective one. These results underscore the importance of ecological measures to precisely investigate each subcomponent of social cognition in alcohol-dependent individuals. They further show that alcohol dependence is closely associated with emotional-affective impairments, pointing to the need to develop rehabilitation progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 60 publications
1
29
0
1
Order By: Relevance
“…Regarding decoding abilities, these results thus support our initial hypothesis that ADI present deficits in identifying affective mental states, even when a complementary social context is available. They thus agree with prior findings suggesting that ADI have impaired abilities in mentalizing affective mental states (Amenta et al., ; Maurage et al., ; Thoma et al., ) and lower performances in recognizing uncontextualized basic and complex emotional states (Maurage et al., , ; Nandrino et al., ) compared to CI. Specifically, the present study provides new information by showing that when participants have more visual information (i.e., not limited to eye gaze), ADI are still impaired in recognizing the facial expressions of complex affective mental states.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding decoding abilities, these results thus support our initial hypothesis that ADI present deficits in identifying affective mental states, even when a complementary social context is available. They thus agree with prior findings suggesting that ADI have impaired abilities in mentalizing affective mental states (Amenta et al., ; Maurage et al., ; Thoma et al., ) and lower performances in recognizing uncontextualized basic and complex emotional states (Maurage et al., , ; Nandrino et al., ) compared to CI. Specifically, the present study provides new information by showing that when participants have more visual information (i.e., not limited to eye gaze), ADI are still impaired in recognizing the facial expressions of complex affective mental states.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to the theory of mind (i.e., inferring other people's mental states; Premack and Woodruff, ), ADI present deficits in understanding affective states (e.g., faux pas, irony) (Amenta et al., ; Maurage et al., ; Thoma et al., ) but with a potential preservation of the abilities related to identifying nonaffective states (e.g., false beliefs) (Bosco et al., ; Maurage et al., ; but for contrasting results, see Maurage et al., ), while contradictory results have been found for this ability. On the one hand, ADI are able to correctly understand intentions and thoughts displayed in short videos of social interactions (Maurage et al., ) and to correctly perform a short version of the Strange Stories Test (Bosco et al., ; Happé et al., ), presenting scenarios that require participants to understand characters’ nonemotional mental states (e.g., bluffing, lies, persuasion). On the other hand, some ADI seemed to have impaired abilities in tracking the other person's mental state in a false belief task (Maurage et al., ), while more than 50% of the ADI did not present any deficit on this task.…”
mentioning
confidence: 99%
“…ToM can be divided into (i) affectiveToM, referring to thinking about affective states, feelings, and emotions of others and (ii) cognitiveToM, referring to thinking about cognitive states, beliefs, thoughts, or intentions of others (Shamay‐Tsoory et al., ). A dissociation between impaired affective ToM but preserved cognitive ToM in alcoholism has been observed (Maurage et al., ; Nandrino et al., ).…”
Section: Alcohol‐related Cognitive Impairmentmentioning
confidence: 98%
“…To our knowledge, no research has explored ToM competencies in GD. Nevertheless, it has been shown that people with alcohol use disorder present altered ToM abilities [69] and, more precisely, specific difficulties regarding affective ToM, while cognitive ToM abilities would be preserved [70]. Nevertheless, it is still unknown whether these deficits are linked to the consumption of neurotoxic substances or to addictive behavior.…”
Section: Theory Of Mindmentioning
confidence: 99%